Ixazomib significantly prolongs progression-free survival in high-risk relapsed/refractory myeloma patients - Avet-Loiseau, Hervé; Bahlis, Nizar J; Chng, Wee-Joo; Masszi, Tamas; Viterbo, Luisa; Pour, Ludek; Ganly, Peter; Palumbo, Antonio; Cavo, Michele; Langer, Christian; Pluta, Andrzej; Nagler, Arnon; et al. (Blood, 2017)
Certain cytogenetic abnormalities are known to adversely impact outcomes in patients with multiple myeloma (MM). The phase 3 TOURMALINE-MM1 study demonstrated a significant improvement in progression-free survival (PFS) with ixazomib-lenalidomide-dexamethasone (IRd) compared with placebo-lenalidomide-dexamethasone (placebo-Rd). This preplanned analysis assessed the efficacy and safety of IRd vs placebo-Rd according to cytogenetic risk, as assessed using fluorescence in situ hybridization. High-risk cytogenetic abnormalities were defined as del(17p), t(4;14), and/or t(14;16); additionally, patients were assessed for 1q21 amplification. Of 722 randomized patients, 552 had cytogenetic results; 137 (25%) had high-risk cytogenetic abnormalities and 172 (32%) had 1q21 amplification alone. PFS was improved with IRd vs placebo-Rd in both high-risk and standard-risk cytogenetics subgroups: in high-risk patients, the hazard ratio (HR) was 0.543 (95% confidence interval [CI], 0.321-0.918; P = .021), with median PFS of 21.4 vs 9.7 months; in standard-risk patients, HR was 0.640 (95% CI, 0.462-0.888; P = .007), with median PFS of 20.6 vs 15.6 months. This PFS benefit was consistent across subgroups with individual high-risk cytogenetic abnormalities, including patients with del(17p) (HR, 0.596; 95% CI, 0.286-1.243). PFS was also longer with IRd vs placebo-Rd in patients with 1q21 amplification (HR, 0.781; 95% CI, 0.492-1.240), and in the "expanded high-risk" group, defined as those with high-risk cytogenetic abnormalities and/or 1q21 amplification (HR, 0.664; 95% CI, 0.474-0.928). IRd demonstrated substantial benefit compared with placebo-Rd in relapsed and/or refractory MM (RRMM) patients with high-risk and standard-risk cytogenetics, and improves the poor PFS associated with high-risk cytogenetic abnormalities. This trial was registered at www.clinicaltrials.gov as #NCT01564537.
Keywords: senioři; proporcionální rizikové modely; dvojitá slepá metoda; Thalidomide; Glycine; Proportional Hazards Models; Multiple Myeloma; Double-Blind Method; thalidomid; sloučeniny boru; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; Boron Compounds; Kaplanův-Meierův odhad; Neoplasm Recurrence, Local; Adult; lokální recidiva nádoru; chemorezistence; Lenalidomide; hodnocení výsledků zdravotní péče; mnohočetný myelom; Disease-Free Survival; ženské pohlaví; Humans; Drug Resistance, Neoplasm; dexamethason; Outcome Assessment, Health Care; Chromosome Aberrations; lidé středního věku; chromozomální aberace; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; glycin; Dexamethasone; dospělí; Female; Aged; lenalidomid; přežití bez známek nemoci; lidé; Male